Agranulocytosis‐complicated DRESS with medullar HHV‐6 replication. Issue 10 (26th June 2020) - Lehericey, Margot; Tétart, Florence; Carvalho, Priscille; Bauvin, Olivia; Hervouet, Charles; Joly, Pascal; Hébert, Vivien
Abstract: HHV‐6B is the subtype most often involved in the systemic manifestations of the DRESS, but also in myelosuppression in bone marrow transplant. We report a new observation of its myelosuppressive effect: a case of DRESS complicated by agranulocytosis with detectable HHV‐6 RNA in bone marrow. Abstract : HHV‐6B is the subtype most often involved in the systemic manifestations of the DRESS, but also in myelosuppression in bone marrow transplant. We report a new observation of its myelosuppressive effect: a case of DRESS complicated by agranulocytosis with detectable HHV‐6 RNA in bone marrow.